Evaluasi Ketercapaian Sasaran Mutu Bidang Perawatan Koleksi Bahan Pustaka pada UPA Perpustakaan Universitas Riau Tahun 2024 - Thamrin Hasan; Nurasmi (Perpustakaan Universitas Riau, 2025)
The effectiveness of the physical management and maintenance of library materials is a crucial indicator in ensuring the sustainability of knowledge transfer in university libraries. Therefore, it is important to evaluate the achievement of quality targets to ensure they are not merely an administrative formality. This study aims to descriptively evaluate the achievement of the Collection Care Quality Targets at the Riau University Library UPA in 2024, identify factors inhibiting the handling of damaged books, and formulate strategic improvement recommendations for management. The research method used is a descriptive quantitative approach by analyzing secondary data sourced from the formal document, the Book Repair Recapitulation Form, document number 12-820/Lib.UR/F-09, through observation and descriptive analysis techniques. The results show that the actual annual performance of the preservation unit reached 95%, obtained from the successful restoration of 424 copies of books from a total of 446 damaged collections. This achievement demonstrates that the institution's Quality Target target (at least 80% per year) was successfully exceeded with a performance surplus of 15%. However, monthly analysis shows fluctuations, with the lowest performance point in November (73%), and a backlog of 22 damaged books at the end of the year. The study's conclusions confirm that preservation governance has been very effective, but operational obstacles remain in the form of workflow bottlenecks due to the high complexity of tracking content or missing pages. As a strategic recommendation, libraries are advised to strengthen component logistics management by establishing a digital critical page database system and digitizing reporting control forms into a real-time monitoring dashboard to prevent a backlog of damaged books at the end of the period.